PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN VARIABEL MODERASI KEPEMIMPINAN KEPALA SEKOLAH PADA SEKOLAH DASAR NEGERI UPTD DIKPORA KECAMATAN SAYUNG KABUPATEN DEMAK (Students' Journal of Economic and Management, 2012)
The purpose of this study to determine  the effect of motivation, labor discipline, leadership role moderating effect of motivation on teacher performance,  Test the effect of the principal's leadership role moderating influence on the performance of the work discipline of teachers Research conducted an empirical all elementary public school teachers Technical Unit Office of Education Youth and Sports Kecamtan Sayung Demak numbering 343 people scattered in 44 school. The sampling technique used is proportional random sampling, the samples were taken by 78 teachers, observed variables are independent variable labor discipline and motivation, moderating variables that principal leadership and teacher performance dependent variable. Data analysis techniques in this study using regression analysis and hypothesis testing moderation calculation t test at significance level of 5%.The results were obtained: Work Discipline is not significant positive effect on the performance of elementary school,  Motivation significant positive effect on the performance of elementary school teachers,.Principal Leadership does not strengthen labor discipline effect on teacher performance elementary schools, Principal Leadership does not strengthen the influence of motivation on the performance of elementary school teachers Keyword: Discipline Work, Motivation, Leadership and School head teacher performance